Navigating the Challenges of Technological Advancement: Iqbal’s Philosophical Insights on Moderation and Humanity in the Digital Age - Firnando, Hero Gefthi (UIN Kiai Haji Achmad Siddiq Jember, 2024)
This study delves into the philosophical insights of Muhammad Iqbal regarding the interaction between humanity, moderation, and technology in the digital age. Iqbal’s concept of khudi (selfhood) and his ethical framework provide a valuable lens for exploring contemporary challenges related to digital identity formation, the ethical implications of artificial intelligence, and technology integration into modern society. Using a qualitative research approach, this study employs textual analysis of Iqbal’s original writings and contemporary interpretations to address how his philosophy can inform ethical digital practices. Through thematic analysis and philosophical hermeneutics, the research reveals three primary insights: the transformative nature of technology on self-awareness, the ethical dilemmas arising from technological advancements, and the necessity of balancing technology with human values such as moderation and equality. The findings underscore the relevance of Iqbal’s thoughts in guiding individuals and societies toward responsible and ethical digital interactions. Ultimately, this research contributes to the growing discourse on digital ethics by offering a comprehensive framework grounded in Iqbal’s enduring philosophical principles. Future research prospects are proposed to integrate Iqbal’s teachings into practical applications for promoting digital moderation, equity, and ethical responsibility.